BENIH ANARKISME MAHASISWA DAN MEDIA SOSIAL (Analisis Isi Pesan Twitter Mahasiswa FISHUM UIN Yogyakarta) - Fatma Dian Pratiwi (Profetik: Jurnal Komunikasi, 2013)
Students as agent of change has a role to nation change. Unfortunately, this big duty often cause a dilemma. They used to have emotional approach rather than intellectual. And it arouse to the anarchism. This reflected in Twitter as social media to sound aspiration. For that, the researcher eager to knowt he development of anarchism seed inside Twitter @intelijenuinsuka. Using the content analysis, and the unit analysis is sintacsis unit which is word or symbol. By the end, we have found the result. From the student’s tweet there were 20 tweet that contain the symbol of anarchism invitation. The symbol of the anarchism invitation trough twitter that were appealed to did the opposition to the institution from the student. Broke the rottenness procentage 35 %, Bad Regime 10% , and the coward official 5%. The tweet about a merit without being instructed based on the data shown that attitude without manner 10%,thiswas a twit that have no use to prevent anarchism. The seed of anarchism happen when the no instructed activity, and useless because there were trenchantly without self awareness from each individual. The tweet from living harmony without intervention had the twit there were no freedom to do activity as much as 10 %. This has shown that there were no activity would be difficult to prevent anarchism. The twit from declination toward the need of authority, there were tweet form the crisis of confident as much 10%. This has shown that by the rejection to authority would be hard to prevent anarchism. The twit that shown there were declination to the need of an autorithy as much as 10%.